Pengaruh Quality Of Work Life Terhadap Komitmen Dan Kepuasan Kerja Dengan Moderasi Budaya Organisasi : Studi Pada Dosen Perempuan USN Kolaka - Novi Asriani; Niar Astaginy; Ismanto Ismanto (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine: (1) The effect of Quality of Work Life on commitment to female lecturers at USN Kolaka. (2) The effect of Quality of Work Life on job satisfaction of USN Kolaka female lecturers. (3) The effect of organizational culture moderates the effect of Quality of Work Life on the commitment of USN Kolaka female lecturers. (4) The effect of organizational culture moderates the Quality of Work life on job satisfaction of USN Kolaka female lecturers. This study used a quantitative method. The data collection was observation, documentation, and questionnaires. The population of this study were all female lecturers at USN Kolaka, totaling 109 female lecturers. The sample of this study was 109 female lecturers. The instrument used were validity and reliability tests with SPSS 25.0. The data analysis technique used in this study was the measurement model test (outer model) and the structural model test (inner model) with Smart PLS 4.0. The results of the study show that there it is a positive and significant influence between the Quality of Work Life variable on commitment as shown by the P-Value of 0.000. Like wise, the variable Quality of Work Life has a positive and significant effect on job satisfaction as indikated by the P-Value of 0.019. Where as the moderation, organizational culture does not moderate Quality of Work Life towords commitment, this is indicated by the t-statistic value showing a value of 0.882 with a P-Value of 0.220. Furthermore, the moderation of organizational culture does not moderate Quality of Work Life on job satisfaction, this is indicated by the t-statistic value showing a value of 0.774 with a P-Value of 0.189.